Micro-drive and headgear for chronic implant and recovery of optoelectronic probes - Chung, Jinho; Sharif, Farnaz; Jung, Dajung; Kim, Soyoun; Royer, Sebastien (NATURE PUBLISHING GROUP, 2017)
Silicon probes are multisite electrodes used for the electrophysiological recording of large neuronal ensembles. Optoelectronic probes (OEPs) are recent upgrades that allow, in parallel, the delivery of local optical stimuli. The procedures to use these delicate electrodes for chronic experiments in mice are still underdeveloped and typically assume one-time uses. Here, we developed a micro-drive, a support for OEPs optical fibers, and a hat enclosure, which fabrications consist in fitting and fastening together plastic parts made with 3D printers. Excluding two parts, all components and electrodes are relatively simple to recover after the experiments, via the loosening of screws. To prevent the plugging of OEPs laser sources from altering the stability of recordings, the OEPs fibers can be transiently anchored to the hat via the tightening of screws. We test the stability of recordings in the mouse hippocampus under three different conditions: acute head-fixed, chronic head-fixed, and chronic freely moving. Drift in spike waveforms is significantly smaller in chronic compared to acute conditions, with the plugging/unplugging of head-stage and fiber connectors not affecting much the recording stability. Overall, these tools generate stable recordings of place cell in chronic conditions, and make the recovery and reuse of electrode packages relatively simple.
Keywords: LARGE-SCALE; NEURAL ACTIVITY; SILICON PROBES; HIGH-DENSITY; OPTICAL TECHNOLOGIES; LOCAL CIRCUITS; PLACE CELLS; NEURONS; DYNAMICS; SENSORS